Uji Coba Pembuatan Limbah Whey Dangke Menjadi Olahan Sorbet - Dewi Andriani; Siti Hadija; Rafika Hayati (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2019)
Whey dangke is a waste generated by proses of separation whey and curd during process of making dangke. This study aims to determine whey of dangke used as dairy product, such as sorbetacceptance of the community to taste, aroma, color and texture of milk sorbet from processed whey dangke Enrekang. Population in this research is student of class 4 Polytechnic of Bosowa. The sample in this research is 73 panelists using simple random sampling technique. This type of research is experimental. The analysis in this study is descriptive statistics using the average formula. whey dangke in this experiment researcher use three types of treatment that is at first treatment W100:S0 (100% whey dangke and 0% pure milk), second treatment W75: S25 (75% whey dangke and 25% pure milk ), the third treatment of W50:S50 (50% whey dangke and 50% pure milk). The results showed that whey dangke Enrekang can be processed as sorbet. Hedonic test on milk sorbet product showed that the most preferred taste aspect was the W50:S50 treatment with an average of 3.46%, the most preferred treatment of the texture aspect was the W50: S50 treatment with an average of 3.75 , the most preferred treatment of the color aspect was the W50: S50 treatment with an average of 3.40, and the most preferred treatment of the aroma aspect was the W100:S0 treatment with an average value of 3.77.